Generation of Amelx-iCre Mice Supports Ameloblast-Specific Role for Stim1. (August 2019) - Said, R.; Zheng, L.; Saunders, T.; Zeidler, M.; Papagerakis, S.; Papagerakis, P.
The identification and targeting of the molecular pathways regulating amelogenesis is an ongoing challenge in dental research, and progress has been restricted by the limited number of genetic tools available to study gene function in ameloblasts. Here, we generated 4 transgenic Cre -driver mouse lines that express improved Cre ( iCre )–recombinase from the locus of the mouse ameloblast-specific gene amelogenin X ( Amelx-iCre ) with a large (250-kb) bacterial artificial chromosome DNA vector. All 4 Amelx-iCre transgenic lines were bred with ROSA26 reporter mice to characterize the iCre developmental pattern with the LacZ gene encoding β-galactosidase enzyme activity assay and Cre protein immunohistochemistry. From the 4 generated transgenic lines, 2 were selected for further analysis because they expressed a high amount of Cre recombinase exclusively in ameloblasts and showed developmental stage- and cell-specific β-galactosidase activity mimicking the endogenous amelogenin expression. To test the functionality of the selected transgenic models, we bred the 2 Amelx-iCre mice lines with stromal interaction molecule 1 ( Stim1 ) floxed mice to generate ameloblast-specific Stim1 conditional knockout mice ( Stim1 cKO ). STIM1 protein serves as one of the main calcium sensors in ameloblasts and plays a major role in enamel mineralization and ameloblast differentiation. Amelx-iCre mice displayed exclusive CRE-mediated recombination in incisor and molar ameloblasts. Stim1 cKO mice showed a severely defected enamel phenotype, including reduced structural integrity concomitant with increased attrition and smaller teeth. The phenotype and genotype of the Amelx-iCre/Stim1 cKO showed significant differences with the previously reported Ker14 - Cre / Stim1 cKO, highlighting the need for cell- and stage-specific Cre lines for an accurate phenotype-genotype comparison. Furthermore, our model has the advantage of carrying the entire Amelx gene locus rather than being limited to an Amelx partial promoter construct, which greatly enhances the stability and the specificity of our Cre expression. As such, the Amelx-iCre transgenic lines that we developed may serve as a powerful tool for targeting ameloblast-specific gene expression in future investigations.